ESENSI BUDAYA BUGIS TERHADAP PRODUK PERATURAN DAERAH DI PAREPARE - Fikri, Fikri; Damirah, Damirah; Tenripadang, Andi (P3M STAIN Parepare, 2016)
Culture is often the reason to create peace, order, order of coolness in society. Culture that will be meaningful and valuable, culture can serve as a source o behavioral determinants and aspiration of society, namely in political and law. Culture only as accessories when placed or be interpreted as a heritage without involving cultural awareness in legal elements for the manufacture of local regulation. Bugis was one tribe that owns and instill cultural values are very high in every movement, behaviour, actions and words. Accordingly the importance of culture became a major ingredient in the making of local regulations, including the town Parepare. Goverment should promote culture as one consideration local rulemaking.